Phylogenetic Relationship Of The Selected Species Of Family Sylviidae Inferred From Partial Mitochondrial Dna (Mtdna) Cytochrome Oxidase I (Coi) Gene - Tan, Kok Peng (Universiti Malaysia Sarawak (UNIMAS), 2009)
The phylogenetic relationship of selected species of birds (Family: Sylviidae) was performed using mitochrondrial DNA (mtDNA) from the partial Cytochrome Oxidase I (COi) gene. In this study, six species namely, Yellow-bellied Prinia (Prinia flaviventris), Rufous-tailed Tailorbird (Orthotomus sericeus), Arctic Warbler (Phylloscopus borealis), Sunda Bush-warbler (Cettia vulcania), Mountain Leaf-warbler (Phylloscopus trivirgatus) and Yellow-breasted Warbler (Seicercus montis) used in constructing the phylogenetic relationship. Chestnut-crested Yuhina (Yuhina everetti) from Family Timaliidae was used as outgroup. Total length of 468 bp sequences of these species was used to construct a phylogenetic tree. From the phylogenetic tree, the selected species from family Sylviidae were divided into five genera, with two major groups. Genus Phylloscopus and genus Seicercus formed in the same group. Another group consisted of genus Prinia, genus Orthotomus and genus Cettia. Analyses of the relationship among these species were based on pairwise distance, neighbor-joining (NJ), maximum parsimony (MP) and maximum likelihood (ML). NJ produced difference topology compared to MP and ML. MP and ML produced similar topology but with different bootstrap values. This study showed that partial COi gene is useful in determining phylogenetic relationship among species and genera of the family Sylviidae.